Capacity, legitimacy or hegemony? A multi-tier explanation for NATO's involvement in the Libya crisis. (2nd October 2017) - Reykers, Yf
Abstract : Although numerous regional (security) organisations have implemented UNSC-authorised military operations, we do not yet know which considerations prevail in the decision to work through a particular organisation. This article introduces a framework consisting of a capacity, legitimacy and hegemony logic for explaining the selection of a regional organisation. The article takes a rational-institutionalist approach, suggesting that analysis should primarily focus on the cost-benefit analyses of states. It applies the framework to NATO's involvement in the Libya crisis (2011). Using insights from policy documents and 31 elite interviews, it shows that thoroughly explaining NATO's involvement is only possible by taking into account all three logics.